Forensic Assistance Project: Consultant Report 1999-022 Čemerno I Republika Srpska Commission on Tracing Prisoners and Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Boaz, Noel On 27-29 May 1999 a mass grave containing 19 bodies was exhumed at the eastern edge of Čemerno Cemetery, a remote Serbian Orthodox Cemetery located near the summit of Čemerska Planina. All individuals within the mass grave reputedly died on 10 June 1992 during or following the fall of a local village to BiH Army forces. The individuals buried in this mass grave were reportedly killed on 10 June 1992 in or following a battle with the BiH Army at the end of a siege of a local village. Place of Exhumation: Čemerno Date of Exhumation: 27-29 May 1999 Minimum Number of Exhumed Individuals: 019